Fluorogenic thiazole orange TOTFO probes stabilise parallel DNA triplexes at pH 7 and above - Walsh, S; El-Sagheer, A; Brown, T (Royal Society of Chemistry, 2018)
The instability of DNA triplexes particularly at neutral pH and above severely limits their applications. Here, we demonstrate that the introduction of a thiazole orange (TO) intercalator onto a thymine nucleobase in triplex forming oligonucleotides (TFOs) resolves this problem. The stabilising effects are additive; multiple TO units produce nanomolar duplex binding and triplex stability can surpass that of the underlying duplex. In one example, a TFO containing three TO units increased the triplex melting temperature at pH 7 by a remarkable 50 °C relative to the unmodified triplex. Notably, TO intercalation promotes TFO binding to target sequences other than pure polypurine tracts by the use of 5-(1-propynyl)cytosine (pC) against C:G inversions. By overcoming the instability of triplexes across a broad range of pH and sequence contexts, these very simple ‘TOTFO’ probes could expand triplex applications into many areas including diagnostics and cell imaging.